Finance and Development, June 2015. (Finance and Development; Finance and Development ;, 2015)
This chapter takes stock of the world's development agenda, examining how to best seize this opportunity. Government officials and representatives from civil society organizations, donor groups, and the private sector are scheduled to meet in Addis Ababa, Ethiopia, to secure the financing needed to lift millions out of extreme poverty. Participants at the United Nations summit on climate change in Paris are expected to work toward a set of environmental targets aimed at ensuring a sustainable future. The chapter also presents an argument that the world needs strong deals in Addis Ababa on financing and in Paris on climate to deliver sustainable progress.